A Cosmopolitan Ethos for Our Future Lawyers - Antonios Platsas (Право. Журнал Высшей школы экономики, 2015)
This article advocates the strengthening of the spirit of cosmopolitanism in modern legal education. In contrast to the epistemic environment of predominantly domestic and nation-oriented discourses across law schools and faculties around the world, the analysis proceeds with a number of propositions as to what ought to be done to improve legal education, especially at first-degree level. Relevant propositions are set out under a proposed cosmopolitan ethos for law. Recognition is given to current fundamentals of legal education and the fact that law is still a predominantly domestic discipline, which is otherwise this contribution’s hypothesis. The article posits that a certain re-alignment of the subject’s overall educational ethos ought to materialise for the benefit of the discipline, as well as for the benefit of future law graduates.To this effect, the author argues that it is the ethos of cosmopolitanism which ought to be directly introduced to the academic learning of law. Accordingly, this essay acts as an invitation for the re-invigoration of liberal education in law in accordance with a new ethos of excellence, a cosmopolitan ethos. Moreover, whilst partial recognition is given to the need for the mastery of positive law amongst law graduates, this contribution attempts to differentiate itself from current legal orthodoxy in educational terms in that it expects and proposes the combination of mastery of positive law with a cosmopolitan ethos in the orders of our future law graduates.